Association of Myocardial Enzyme Abnormality with Clinical Outcomes of Patients with COVID-19: A Retrospective Study. (22nd October 2021) - Zhang, Qilin; Zheng, Ziming; Zhang, Yu
Abstract : Background . It has been observed that COVID-19 may cause myocardial damage, but there are few detailed reports on myocardial enzyme abnormalities. Methods . In this retrospective study, we analyzed data from 157 consecutive laboratory-confirmed and hospitalized COVID-19 patients from Wuhan. We collected information on demographic and clinical characteristics, laboratory findings, and clinical outcomes. Logistic regression analysis was used to explore the risk factors associated with the severity of COVID-19. The association between myocardial enzyme abnormalities and the mortality was also investigated. Results . The mortality in abnormal myocardial enzyme group was obviously higher than the normal group (P < 0.001 ). The majority of patients (n = 72, 97.3%) with normal cardiac enzyme group were of the common novel coronavirus pneumonia (NCP) type, whereas half of the patients with cardiac enzyme abnormalities (n = 40, 48.2%) developed critical and severe NCP type. The multivariable logistic regression analysis indicated that COVID-19 patients with increasing age (P = 0.035 ), higher levels of CRP (P = 0.038 ), and TNI (P = 0.036 ) were associated with increased death than other patients. Conclusions . Myocardial enzyme abnormality and myocardial injury were associated with the severity and fatal outcomes of COVID-19. Clinicians should pay attention to the markers of myocardial injury in COVID-19 patients, especially those with older age, comorbidities, and inflammation.